The 'Spinster' and her Jellyfish: Dorothy's Cross Medusae (2003) and historiographical storytelling. Issue 5 (20th October 2022) - Elstob, Isobel
Abstract : This essay analyses Dorothy Cross's 2003 video work Medusae in relation to late-twentieth-century literary reworkings of the historical past A visual representation of the obscure woman naturalist Maude Delap, Medusae is argued here to function as historiographic montage, interrogating and celebrating the possibility of visualising an historical life through visual art. Using established literary models including intertextuality and dialogic structuring, the essay presents Medusae as an important example of visual art's response to debates surrounding historiography and creative representations of the past through making a detail analysis of how its elements and forms mediate a specific historical life in 'the present'.